Determinantes da produtividade dos gerentes de negócios no setor financeiro – um estudo de caso - Vivas, Luis Augusto Silva (2016)
The study investigates relevant factors on business managers’ productivity of a large international bank, in a case study for a sample of 89 managers of the regional Fortaleza. Econometric models were estimated in two periods which were 2013 and 2014 and the results enable us to conclude that variables such goals, training, number of customers and time in the position were significant for the increasing of managers’ productivity. Managers and professionals in the field of human resources of companies, through this study, can benefit from greater assertiveness in managing their human capital, maximizing the opportunities of increasing their productivity, reducing turnover of people and improving the quality of hiring processes for internal transfers, promotions and hiring.